A comparative analysis of perceptual and demographic predictors of sense of place dimensions in the State Mosques of Malaysia. Issue 2 (June 2014) - Mazloomi, Seyed Maziar; Ariffin, Syed Iskandar; Shahminan, Raja Nafida Raja
<x xml:space="preserve">Abstract</x> The study in this article is part of a more in‐depth research investigating the architectural and physical design influences on sense of place dimensions in the context of contemporary mosques in Malaysia. The focus of this paper is human–place bonding in sacred and religious settings, based on a framework including aspects of sociality, physicality and spirituality, in addition to demographic variables such as ranges of length of experience with, and frequency of presence in, the environment of the studied mosques. The effects of the perceptions of architecture and physical design, social environment, and spiritual atmosphere on dimensions of sense of place were studied using a structural equation modelling analysis based on 302 questionnaires completed in seven state mosques across the Southeast Asian country of Malaysia. Meanwhile the socio‐demographic effects on sense of place dimensions were also tested based on several analyses of variances (ANOVA) in various demographic groups through sense of place dimensions. In doing so, we adopted the multi‐dimensional approach towards sense of place consisting of cognitive, affective, and behavioral dimensions. As major findings, this research provided empirical evidence for the existence of direct relationships between perceptions of the key environmental factors studied and the sense of place dimensions in contexts with extensive religious and sacred attributes; on the other hand, no interactive relationship was found between most of the socio‐demographic variables and those dimensions. This article discusses in detail each of those approved and rejected relationships.